Question
Simplify the expression completely: \( \frac{\left(2 x^{3}\right)^{2}}{x^{-5}}=\square \)
Ask by Mckenzie Watkins. in the United States
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\(4x^{11}\)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Mind Expander
To simplify the expression \( \frac{\left(2 x^{3}\right)^{2}}{x^{-5}} \), start by calculating the numerator: \((2 x^{3})^{2} = 2^{2} (x^{3})^{2} = 4 x^{6}\). Now, rewrite the entire expression: \(\frac{4 x^{6}}{x^{-5}}\). Next, utilize the property of exponents that states \( \frac{a^{m}}{a^{n}} = a^{m-n} \): \(\frac{4 x^{6}}{x^{-5}} = 4 x^{6 - (-5)} = 4 x^{6 + 5} = 4 x^{11}\). So, the simplified expression is: \(4 x^{11}\).